Early suspicion can save lives; mucormycosis in two children with diabetic ketoacidosis in Pakistan. - Ayesha Shahid; Batool Fatima; Yasir Naqi Khan; Mohsina Noor Ibrahim; Jamal Raza (Journal of the Pakistan Medical Association, 2022)
Background: Mucormycosis is a cause of fulminant necrotizing fungal infection in children with underlying immunocompromising condition. Rhino-orbito-cerebral infection is the most common form of mucormycosis in children with uncontrolled diabetes mellitus or diabetic ketoacidosis. Once considered a rare entity is now increasingly being reported especially in the diabetic population. The initial presentation can mimic a bacterial infection, thus a high index of suspicion is needed for timely intervention to reduce morbidity and mortality. Case report: We present a case of rhino-orbito-cerebral mucormycosis in two patients with diabetic ketoacidosis for the first time from Pakistan. Both the patients couldn’t survive due to late and extensive disease on presentation. Keywords: mucormycosis; rhino-orbito-cerebral mucormycosis; diabetic ketoacidosis; diabetes mellitus, pediatric; children